Inhibitory effects of oxytocin and oxytocin receptor antagonist atosiban on the activities of carbonic anhydrase and acetylcholinesterase enzymes in the liver and kidney tissues of rats - Gülçin, İlhami; Taslimi, Parham; Koçyiğit, Ümit M.; Taşkıran, Ahmet Şevki; Yokus, Ahmet; Temel, Yusuf; Taslimi, Parham (Wiley, 2017)
The aim of this study was to investigate the effects of oxytocin (OT), atosiban, which is an OT receptor antagonist, and OT-atosiban chemicals injected to rats on the activities of carbonic anhydrase (CA) and acetylcholinesterase (AChE) enzymes in liver and kidney tissues of rats. For this purpose, four different groups, each consisting of six rats (n=6), were formed (control group, OT administered group, atosiban administered group, and both OT and atosiban administered group). The rats were necropsied 60min after intraperitoneal injection of chemicals into the rats. Liver tissues of rats were extracted. CA and AChE enzyme activities were measured for each tissue by using hydratase, esterase, and acetylcholiniodide methods. Activity values for each enzyme obtained were statistically calculated.
Keywords: Enzyme activity; Carbonic anhydrase; Oxytocin; Rat